Tìm x biết | x + 2 | - 4 = 6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 1 : a,ta có 3/x-1 =4/y-2=5/z-3 => x-1/3=y-2/4=z-3/5
áp dụng .... => x-1+y-2+z-3 / 3+4+5 = x+y+z-1-2-3/3+4+5 = 12/12=1
do x-1/3 = 1 => x-1 = 3 => x= 4 ( tìm y,z tương tự
Bài 1:
a) Ta có: 3/x - 1 = 4/y - 2 = 5/z - 3 => x - 1/3 = y - 2/4 = z - 3/5 áp dụng ... =>x - 1 + y - 2 + z - 3/3 + 4 + 5 = x + y + z - 1 - 2 - 3/3 + 4 + 5 = 12/12 = 1 do x - 1/3 = 1 => x - 1 = 3 => x = 4 ( tìm y, z tương tự )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3:
a: 3^x*3=243
=>3^x=81
=>x=4
b; 2^x*16^2=1024
=>2^x=4
=>x=2
c: 64*4^x=16^8
=>4^x=4^16/4^3=4^13
=>x=13
d: 2^x=16
=>2^x=2^4
=>x=4
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>x=3/7+3/5=15/35+21/35=36/35
b: =>x/35=4/5-5/7=28/35-25/35=3/35
=>x=3
c: =>x<3/4+8/4=11/4
=>\(x\in\left\{0;1;2;3\right\}\)
d: =>5/3<x<5/6+24/6=29/6
=>\(x\in\left\{2;3;4\right\}\)
e: =>x<10/12-9/12=1/12
=>x=0
f: =>2/3<x<12/6-5/6=7/6
=>x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
1a) \(\frac{x-3}{x+7}=\frac{-5}{-6}\)
=> \(\frac{x-3}{x+7}=\frac{5}{6}\)
=> (x - 3).6 = 5.(x + 7)
=> 6x - 18 = 5x + 35
=> 6x - 5x = 35 + 18
=> x = 53
b) \(\frac{x-7}{x+3}=\frac{4}{3}\)
=> (x - 7). 3 = (x + 3). 4
=> 3x - 21 = 4x + 12
=> 3x - 4x = 12 + 21
=> -x = 33
=> x = -33
c) \(\frac{x-10}{6}=-\frac{5}{18}\)
=> (x - 10) . 18 = -5 . 6
=> 18x - 180 = -30
=> 18x = -30 + 180
=> 18x = 150
=> x = 150 : 18 = 25/3
d) \(\frac{x-2}{4}=\frac{25}{x-2}\)
=> (x - 2)(x - 2) = 25 . 4
=> (x - 2)2 = 100
=> (x - 2)2 = 102
=> \(\orbr{\begin{cases}x-2=10\\x-2=-10\end{cases}}\)
=> \(\orbr{\begin{cases}x=12\\x=-8\end{cases}}\)
e) \(\frac{7}{x}=\frac{x}{28}\)
=> 7 . 28 = x . x
=> 196 = x2
=> x2 = 142
=> \(\orbr{\begin{cases}x=14\\x=-14\end{cases}}\)
f) \(\frac{40+x}{77-x}=\frac{6}{7}\)
=> (40 + x) . 7 = (77 - x).6
=> 280 + 7x = 462 - 6x
=> 280 - 462 = -6x + 7x
=> -182 = x
=> x = -182
![](https://rs.olm.vn/images/avt/0.png?1311)
=x(x+2)-3(x+2)=4(x+2)=(x+2)(x-3)=4(x+2)<=>(x-3)=\(\frac{4\left(x+2\right)}{x+2}\)=4<=>x=7.vay x=7
Xx+2)-(3x+6)=4(x+2)
x(x+2)-3(x+2)=4(x+2)
(x-3)(x+2)=4(x+2)
4(x+2)-(x-3)(x+2)=0
(4-x-3)(x+2)=0
(1-x)(x+2)=0
SUY ra :1-x=0 hoac x+2=0
nen x=1 hoac x=-2
vay x= 1 hoac x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)